Solar fields in farmlands, their impact on bat presence and activity - Chloé Tavernier; Rascha Nuijten; Ralph Buij; Frank van Langevelde (PLoS ONE, 2026)
Bat populations are facing numerous challenges due to human activities, and the development of solar energy in agricultural landscapes may add to these issues. Effects of solar fields on bat populations are still poorly understood. In this study, we compared bat activity in six solar fields that each had two grassland controls (agricultural grassland and natural meadows). Using passive bat detectors, bat calls were recorded along the edges of these plots, where the highest bat species diversity and activity were expected. The effects of landscape composition and configuration on the diversity, presence, and activity of different bat species were evaluated for each plot type at yearly, seasonal, and monthly scales. All seven bat species studied were less active in the solar fields compared to the two grassland controls. Specifically, both the number of nights that bats were present and the activity of bats were reduced in solar fields. As the number of solar fields keeps increasing in the agricultural landscape, it is thus essential to monitor their effect on the population levels.